Pollination syndrome and breeding system of four reforestation tree species in Mt. Makiling, Luzon, Philippines - Escobin, Ramiro P. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2004)
The pollination syndrome and breeding system of four reforestation tree species in Mt. Makiling, Laguna Province in Southern Luzon, Philippines, namely; Acacia auriculiformis Cunn. ex Benth. (auri), Vitex parviflora Juss. (molave), Leucaena leucocephala (Lam.) de Wlt (ipil-ipil, El Salvador Strain) and Pterocarpus indicus Willd.1 (narra) were investigated. Floral buds were enclosed with pollination bags and nets to exclude insect visitors/ pollinators of each species, with a corresponding number of buds tagged and left open to serve as control. The inflorescence of L. leucocephala was enclosed with paper packets to exclude floral visitors and wind-borne pollen grains. Results of the pollination bag experiments suggested that A. auriculiformis, V. parviflora and P. indicus were out crossing and entomophilous. Important pollinators of the species were medium- to large-sized bees. Floral morphology exhibited the bee floral syndrome. leucaena leucocephala is self-compatible and shows floral characteristics for anemophily. The rest of the species studied is self-incompatible and dichogamous.